Waypoints : my Scottish journey - Heughan, Sam, 1980- (Voracious, Little, Brown and Company, 2022)
"Journey deep into the Scottish Highlands in the first memoir by #1 New York Times bestselling author and star of Outlander, Sam Heughan--exploring his life and reflecting on the waypoints that define him. In this intimate journey of self-discovery, Sam sets out along Scotland's rugged ninety-six-mile West Highland Way to map out the moments that shaped his views on dreams and ambition, family, friendship, love, and life. The result is a love letter to the wild landscape that means so much to him, full of charming, funny, wise, and searching insights into the world through his eyes"--